SUBSURFACE CHARACTERIZATION USING GEOPHYSICAL TECHNIQUES FOR THE RECONSTRUCTION OF ST. FINBARR’S COLLEGE ROAD, SOUTHWESTERN NIGERIA - Anukwu, Geraldine Chibuzor; Ifarajimi, Williams T.; Okuzor, Chiekem A.; Abdulkadir, Zainab (FUDMA Journal of Sciences, 2024)
The St. Finbarr’s College Road connects a number of educational institutions, including the University of Lagos, Akoka, to the northern part of Lagos. Rehabilitation work on the road revealed the presence of peat and clay at some locations, prompting the need to define the extent of their occurrence. In this study, geophysical techniques consisting of the Multichannel Analysis of Surface Waves (MASW) and Electrical Resistivity measurements were conducted on six traverses established along the road to characterize the subsurface and identify zones of instability. The resistivity and shear wave velocity (Vs) values obtained vary along the traverses, suggesting heterogeneity in the soil composition of the area. Specifically, the top 2m is generally characterized by materials having a resistivity less than 50 ohm-m and Vs greater than 200 m/s, which has been interpreted as a relatively stiff clay. However, a small number of spots on traverses 1 and 2 have low Vs (> 200 m/s), which suggests less stiff material and possible weak zones. Although the Vs values suggest that the upper 2m of the subsurface is characterised by materials considered to be stiff soil, its clayey nature might pose a challenge to the stability of the pavement, as clay materials are generally considered to be a problematic engineering material. To prevent the failure of the road, the soil parameters obtained in this study should be taken into account during reconstruction.